Stock market index price prediction using predetermined variables: a case study of Malaysia - Qaiser Munir; Sook, ching Kok (2016)
The EMH states that security prices fully reflect the available information (Fama, 1970, 1991). The weak-form EMH asserts that security prices already fully reflect the information contained in the history of past trading Stock market efficiency in the weak-form sense has been widely studied and the methodologies being used are various. These include the tests used for assessing the stochastic properties of stock prices and the tests under the rubric of return predictability (Fama, 1991). On return predictability in particular, one strand of the literature attempts to predict the movements of stock prices using predetermined variables, most often by employing the data of macroeconomic variables and commodity prices.